Narrative review: status of key performance indicators in contemporary hospital pharmacy practice. (December 2015) - Lloyd, Georgia F.; Bajorek, Beata; Barclay, Peter; Goh, Sue
Abstract: Aim: The aim of this review was to explore the status of key performance indicators (KPIs) in Australian hospital pharmacy practice. Data sources: For this narrative review, databases (MEDLINE, PubMed and EBSCO) were searched for relevant publications within the period from April 1980 to April 2014 using the following search terms: hospital pharmacy, key performance indicators, performance measures, clinical indicators and benchmarking. The inclusion criteria were as follows: full text papers (papers only available as abstracts were discarded) and English language. Reference lists of selected papers were also searched to identify additional literature. Results: While there are established competencies, standards and quality use of medicines (QUM) indicators for hospital pharmacy in Australia, there are no standardised KPIs relating to the performance and practice of hospital pharmacy. International research has demonstrated that KPIs are valuable tools for measuring pharmacy performance; the need for KPIs is highlighted in research from the UK, USA, Canada, New Zealand and Australia. Particular challenges associated with KPI implementation include: the need for relevance to all stakeholders; difficulties in measuring pharmacists' activities due to the inherent nature of their work; lack of resources for data collection; limited understanding of KPIs; and negative attitudes toward KPIs by some pharmacists. Conclusion: Before nationally standardised KPIs are introduced into Australian hospital pharmacy practice, attention must be paid to developing relevant measures through careful consultation with all relevant stakeholders, including pharmacists themselves. KPIs should provide relevant results, be easy to measure and highlight the value of hospital pharmacy services in a resource‐friendly manner.